Laparoscopic Cholecystectomy in a Day Case Setting: A Ganga Ram Hospital Experience - HINA KHAN; ASLAM JAVED; MUHAMMAD TANVEER, SHAHZAD ALAM SHAH; MUHAMMAD ARSHAD; (Journal of Fatima Jinnah Medical University, 2018)
Because of the early recovery after Laparoscopic Cholecystectomy, this procedure is now being performed in day care settings. This study was conducted to determine the feasibility, rate and type of complications associated with laparoscopic cholecystectomy as a day case procedure without compromising the health of the patients. Material and Methods: This study was conducted in the Department of General Surgery Sir Ganga Ram Hospital, Lahore from December, 2010 till December, 2012. Seventy five patients of mixed gender were included in the study. Sampling Technique: Convenience sampling technique was employed Study Design: It was a cross sectional descriptive study conducted from December 2010 to December, 2012. Results: Seventy five patients with gallstone disease fulfilling the inclusion criteria were selected for this study. The female: male ratio was 57:18 and age range for female was 20-65 years (mean 35.44 years) and for male was 32-65 years (mean 40.14). The majority of the patients (86%) presented with biliary colic and 14% patient with acute cholecystitis was included in the study. In sixty two (82.66%) of selected patients day case laparoscopic cholecystectomies were successfully performed. Thirteen patients (17.33%) required an overnight stay. Overall complication rate was found at 16 percent (n=12). No major complication and no mortality occurred during the study period. Conclusion: Our results showed that laparoscopic cholecystectomy could be performed as day case in our setup in carefully selected patients with good patient satisfaction.